A physical-chemical and theoretical-practical analysis of icebergs (Research, Society and Development, 2024)
This research aims to present a theoretical-practical discussion about icebergs through a simple experimental design, with low-cost materials, exemplified by the system consisting of an ice cube inserted into a glass of drinking water. We sought to verify the effects of water temperature and solution concentration on the melting process, to then correlate with external conditions that could or could not favor the melting of icebergs. To achieve the proposed objective, ice cubes were removed from the freezer and then inserted into containers that contained liquid water at different temperatures. The second experimental design involved inserting the cube into solutions with different concentrations of sodium chloride, the results of which were compared to those of drinking water. Comparative analysis indicated that reducing the temperature of the water to which the ice was added increased the time required to complete melting. On the other hand, when the temperature was maintained, it was evident that the addition of sodium chloride increased the necessary time interval. The importance of developing this work is highlighted, since the analysis of the results will be able to answer questions about everyday facts related to floating blocks of ice.